10yp-35p-24yx+49x=

Simple and best practice solution for 10yp-35p-24yx+49x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10yp-35p-24yx+49x= equation:


Simplifying
10yp + -35p + -24yx + 49x = 0

Reorder the terms:
-35p + 10py + 49x + -24xy = 0

Solving
-35p + 10py + 49x + -24xy = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-49x' to each side of the equation.
-35p + 10py + 49x + -49x + -24xy = 0 + -49x

Combine like terms: 49x + -49x = 0
-35p + 10py + 0 + -24xy = 0 + -49x
-35p + 10py + -24xy = 0 + -49x
Remove the zero:
-35p + 10py + -24xy = -49x

Add '24xy' to each side of the equation.
-35p + 10py + -24xy + 24xy = -49x + 24xy

Combine like terms: -24xy + 24xy = 0
-35p + 10py + 0 = -49x + 24xy
-35p + 10py = -49x + 24xy

Reorder the terms:
-35p + 10py + 49x + -24xy = -49x + 49x + 24xy + -24xy

Combine like terms: -49x + 49x = 0
-35p + 10py + 49x + -24xy = 0 + 24xy + -24xy
-35p + 10py + 49x + -24xy = 24xy + -24xy

Combine like terms: 24xy + -24xy = 0
-35p + 10py + 49x + -24xy = 0

The solution to this equation could not be determined.

See similar equations:

| 123×1/3 | | -21x=5 | | 3(2-x)=2(6x-3) | | 3(2x-7)=4(3+x) | | 14x^4+14x^3-x^2-x=0 | | -4x-19=-99 | | 6x-21=12+4x | | 5z-2z=3z-9+8z | | (((1.5b*b))/(1.5b*b))=50 | | 4z/(-16)=-6 | | -1-5s+6s=5 | | (1.5b*b)=50 | | 4p*2q=30 | | 55r^2-14r-23=0 | | 11+4x=7(x-1) | | 5z-9z=-7z-7-z | | 40=x(x+3) | | 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 |

Equations solver categories